Surface chemistry variations among a series of laboratory-produced biochars - Mukherjee, A.; Zimmerman, A.R.; Harris, W. (Geoderma, 2011)
While the idea that adding pyrogenic carbon (referred to as ‘biochar’ when used as a soil amendment) will enhance soil fertility and carbon sequestration has gained widespread attention, understanding of its chemical and physical characteristics and the methods most appropriate to determine them have lagged behind. This type of information is needed to optimize the properties of biochar for specific purposes such as nutrient retention, pH amelioration or contaminant remediation. A number of surface properties of a range of biochar types were examined to better understand how these properties were related to biochar production conditions, as well as to each other. Among biochars made from oak ( Quercus lobata), pine ( Pinus taeda) and grass ( Tripsacum floridanum) at 250 °C in air and 400 and 650 °C under N 2, micropore surface area (measured by CO 2 sorptometry) increased with production temperature as volatile matter (VM) decreased, indicating that VM was released from pore-infillings. The CEC, determined using K + exchange, was about 10 cmol c kg −1 for 400 and 650 °C chars and did not show any pH dependency, whereas 250 °C biochar CECs were pH-dependant and rose to as much as 70 cmol c kg −1 at pH 7. Measurements of surface charge on biochar particles indicated a zeta potential of − 9 to − 4 mV at neutral pH and an iso-electric point of pH 2–3. However, a colloidal or dissolved biochar component was 4–5 times more electronegative. Total acid functional group concentration ranged 4.4–8.1 mmol g −1 (measured by Boehm titration), decreased with production temperature, and was directly related to VM content. Together, these findings suggest that the VM component of biochar carries its acidity, negative charge, and thus, complexation ability. However, not all acid functional groups exchanged cations as the number of cation exchanging sites (CEC) was about 10 times less than the number of acid functional groups present on biochar surfaces and varied with biomass type. These findings suggest that lower temperature biochars will be better used to increase soil CEC while high temperature biochars will raise soil pH. Although no anion exchange capacity was measured in the biochars, they may sorb phosphate and nitrate by divalent cation bridging. ► Biochar surface area mainly in micropores and best measured by CO 2 sorptometry. ► The volatile component of biochar generates biochar acidity and CEC. ► Biochar surface is negatively charged. ► High temperature chars increase soil pH and low temperature chars increase CEC.